Fracture studies on narrow gap welded SA 312 Type 304LN stainless steel straight pipes under quasi-cyclic loading. (July 2019) - Vishnuvardhan, S.; Gandhi, P.; Saravanan, M.; Raghava, G.; Gupta, Suneel K.; Singh, P.K.; Bhasin, Vivek
Abstract: Fracture studies were carried out on narrow gap welded SA 312 Type 304LN stainless steel straight pipes having circumferential through-wall notch in the weld. Totally six specimens were tested; one specimen was subjected to monotonic loading and the remaining five specimens were subjected to quasi-cyclic loading. Under quasi-cyclic loading, one specimen was tested under incremental displacement-controlled loading and the remaining four specimens were tested constant amplitude load-controlled loading. Based on the load-controlled experimental results, a plot of the cyclic load amplitude versus number of cycles to failure of the specimens was obtained. The experimental results indicate that the piping components subjected to quasi-cyclic loading may fail in very less number of loading cycles even when the load amplitude is sufficiently below the monotonic fracture/collapse load. Crack growth behaviour and cyclic tearing instability in the specimens, which are required for realistic assessment of Leak Before Break applicability, was studied. Highlights: Fracture behaviour of through-wall cracked narrow gap welded straight pipes is studied. A plot between cyclic load amplitude and number of cycles to failure of specimens is obtained. Cyclic failure load reduced to 81.5% of the monotonic failure load for resisting 50 loading cycles. Crack growth under load-control was unstable and specimens failed by sudden collapse.